Kepastian Hukum Terhadap Investor Hutan Tanaman Industri Pasca Terbitnya Peraturan Pemerintah Nomor 57 Tahun 2016 Tentang Perubahan Atas Peraturan Pemerintah Nomor 71 Tahun 2014 Tentang Perlindungan Dan Pengelolaan Ekosistem Gambut - Nefi, Arman; Fonger, Suhardi; Akbar, Andy (UI Scholars Hub, 2022)
One of the natural resources that become strategic assets and have economic function to support the development of national economy is forest. Investments in pulp and paper factories certainly depend heavily on the availability of raw materials from plantations that support their production capacity. Therefore, the industrial timber estate businessmen who have been given license certainly have hope that the given area can be used as much as possible. In order to preserve the peat ecosystem, the government in 2014 issued Government Regulation No. 71/2014 tentang Perlindungan dan Pengelolaan Ekosistem Gambut. Under this policy, there will be such land designated as a protected peat ecosystem function, so that business actors whose licensing areas have peat ecosystems are prohibited for land clearing in the peat ecosystem. However Article 45 of Government Regulation No. 71/2014 provides an exception to business actors who have permission before this Government Regulation No. 71/2014 is issued and has conducted activities on such land will remain valid until the license expires. This became a polemic when the Government revised the Government Regulation No. 71/2014 with Government Regulation No. 57/2016. Article 26 paragraph (1) of this Government Regulation prohibits the opening of new land until the establishment of protected functions and cultivation functions in the peat ecosystem area. Option is given by the Government as referred to in Article 8G of Peraturan Menteri LHK No. P.17 / 2017 by providing a replacement land mechanism for IUPHHK-HTI holders whose area is above or equal to 40% designated as peat ecosystem. However, the replacement land criterion is still unclear so it does not provide business certainty to the business actors.